2010
DOI: 10.1074/jbc.m109.057745
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-response Element-binding Protein (CREB) Controls MSK1-mediated Phosphorylation of Histone H3 at the c-fos Promoter in Vitro

Abstract: The rapid induction of the c-fos gene correlates with phosphorylations of histone H3 and HMGN1 by mitogen-and stressactivated protein kinases. We have used a cell-free system to dissect the mechanism by which MSK1 phosphorylates histone H3 within the c-fos chromatin. Here, we show that the reconstituted c-fos chromatin presents a strong barrier to histone H3 phosphorylation by MSK1; however, the activators (serum response factor, Elk-1, cAMP-response element-binding protein (CREB), and ATF1) bound on their cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…Upon BMP-2 addition, we could also detect recruitment of histone H3, phosphorylated at Ser10, into BMP-responsive gene promoters by chromatin immunoprecipitation assays (data not shown). Recently it has been demonstrated that Msk1 should be recruited to responsive promoters by direct interaction with Creb only when phosphorylated at Ser133 (49). Altogether we demonstrate the convergence of Smad and p38 signaling on the activity of specific transcription factors such as Runx2, Atf2, and Creb, that allow the recruitment of coactivators that mediate their effects on Cox2 transcription and likely into other BMP-responsive genes.…”
Section: Discussionmentioning
confidence: 73%
“…Upon BMP-2 addition, we could also detect recruitment of histone H3, phosphorylated at Ser10, into BMP-responsive gene promoters by chromatin immunoprecipitation assays (data not shown). Recently it has been demonstrated that Msk1 should be recruited to responsive promoters by direct interaction with Creb only when phosphorylated at Ser133 (49). Altogether we demonstrate the convergence of Smad and p38 signaling on the activity of specific transcription factors such as Runx2, Atf2, and Creb, that allow the recruitment of coactivators that mediate their effects on Cox2 transcription and likely into other BMP-responsive genes.…”
Section: Discussionmentioning
confidence: 73%
“…One possible explanation for these observations is that Nrf2 may directly or indirectly recruit a H3S10 kinase to the HO-1 ARE, where upon the kinase, associated with chromatin, phosphorylates H3S10. This is not without precedence; it has been demonstrated that transcription factors such as c-myc [56], CREB [57], and Elk1 [58] associate with H3S10 kinases on enhancer regions.…”
Section: Discussionmentioning
confidence: 99%
“…MSK1 and MSK2 activation acts as a feedback control mechanism to dampen the inflammatory response by up-regulating MKP-1 expression through phosphorylation of several transcription factors, including cAMP-response element-binding protein (CREB) and activating transcription factor 1 (ATF1) (35)(36)(37). Therefore, we assessed whether rapamycin also activates MSKs and their downstream transcription factors.…”
Section: Resultsmentioning
confidence: 99%